-2/3x + 75% -x = -2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(^{x^2}\)= \(\frac{8}{75}:\frac{2}{3}\)
\(x^2\)= \(\frac{4}{25}\)
x = tự làm tiếp nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 4x(x - 5) - (x - 1)(4x - 3) = 5
4x2 - 20x - (4x2 - 3x - 4x + 3) = 5
4x2 - 20x - 4x2 + 3x + 4x - 3 = 5
-13x - 3 = 5
\(\Rightarrow\) -13x = 8
\(\Rightarrow\) x = \(\dfrac{-8}{13}\)
b) (3x - 4)(x - 2) = 3x(x - 9) - 3
3x2 - 6x - 4x + 8 = 3x2 - 27x - 3
3x2 - 10x + 8 - 3x2 + 27x + 3 = 0
17x + 11 = 0
\(\Rightarrow\) 17x = -11
\(\Rightarrow\) x = \(\dfrac{-11}{17}\)
c) x2 - 81 = 0
\(\Rightarrow\) x2 = 81
\(\Rightarrow\) x = \(\pm\) 9
d) 3x2 - 75 = 0
3(x2 - 25) = 0
\(\Rightarrow\) x2 - 25 = 0
\(\Rightarrow\) x2 = 25
\(\Rightarrow\) x = \(\pm\)5
e) x2 - 4x + 3 = 0
x2 - x - 3x + 3 = 0
(x2 - x) - (3x - 3) = 0
x(x - 1) - 3(x - 1) = 0
(x - 3)(x - 1) = 0
\(\Leftrightarrow\left\{{}\begin{matrix}x-3=0\\x-1=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=3\\x=1\end{matrix}\right.\)
xin lỗi vì chữa đề
![](https://rs.olm.vn/images/avt/0.png?1311)
1)3.x^2 - 75 = 0
3.x^2 - 3.25 = 0
3.(x^2-25)=0
x^2-5^2=0
(x-5)(x+5)=0
=> x-5=0 hoặc x+5=0
=> x=5 hoặc x=-5
1) \(3x^2-75=0\)
\(\Leftrightarrow3\left(x^2-25\right)=0\)
\(\Leftrightarrow x^2-25=0\)
\(\Leftrightarrow x^2=25\)
\(\Leftrightarrow x=\pm\sqrt{25}=\pm5\)
2) \(x^3+9x^2+27x+27=0\)
\(\Leftrightarrow\left(x+3\right)^3=0\)
\(\Leftrightarrow x+3=0\Leftrightarrow x=-3\)
3) \(x^3+3x^2+3x=0\)
\(\Leftrightarrow x^3+3x^2+3x+1=1\)
\(\Leftrightarrow\left(x+1\right)^3=1^3\)
\(\Leftrightarrow x+1=1\Leftrightarrow x=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(-75) : (x + 6) = -15
x + 6 = -75 : (-15)
x + 6 = 5
x = 5 - 6
x = -1
B) -25 - 5.(x + 2) = 50
5(x + 2) = -25 - 50
5(x + 2) = -75
x + 2 = -75 : 5
x + 2 = - 15
x = -15 - 2
x = -17
D) 6.(2x - 8) - 8.(3x - 5) = -56
12x - 24 - 24x + 40 = -56
-12x + 16 = -56
-12x = -56 - 16
-12x = -72
x = (-72) : (-12)
x = 6
Lời giải:
a.
$-75:(x+6)=-15$
$x+6=(-75):(-15)=5$
$x=5-6=-1$
b.
$-25-5(x+2)=50$
$5(x+2)=-25-50=-75$
$x+2=-75:5=-15$
$x=-15-2=-17$
d.
$6(2x-8)-8(3x-5)=-56$
$(12x-48)-(24x-40)=-56$
$-12x-8=-56$
$-12x=-56+8=-48$
$x=(-48):(-12)=4$
\(-\dfrac{2}{3}\cdot x+75\%-x=-2\)
\(x\cdot\left(-\dfrac{2}{3}-1\right)+0,75=-2\)
\(x\cdot\left(-\dfrac{5}{3}\right)=-2-0,75\)
\(x\cdot\left(-\dfrac{5}{3}\right)=-\dfrac{11}{4}\)
\(x=-\dfrac{11}{4}\cdot\left(-\dfrac{3}{5}\right)\)
\(x=\dfrac{33}{20}\)